ASSESSING THE EFFECT OF KITCHEN LAYOUT ON EMPLOYEE’S PRODUCTIVITY - Hagan, Joana Adwoa; Kwofie, Adelaide Spio; Baissie, Faustina (IJRDO - Journal of Applied Management Science, 2017)
A cross sectional survey was conducted to assess the impact of kitchen layout on employees’productivity. A purposive sampling technique was used to select 90 respondents from three (3)company kitchens in the Takoradi Metropolis of Ghana. The samples included all kitchen staffirrespective of their gender, age and position. Data was collected from these respondents using astructured questionnaire and collected data was analyzed using the SPSS software. It was foundout that most of the respondents did not have much knowledge about the concept of kitchenlayout designs. Though a few of the respondents reported that their kitchen layout makes workdifficult, most indicated that the layout of the kitchen they work in makes their work very easy.Majority of them also indicated that their kitchen arrangements gave them enough space tooperate which allowed them to have easy movement from one station to another therebyimproved their working speed. Finally, only half of the respondents said they knew that workingin a poor layout designed kitchens could have some effects such as stress, respiratory problems,bodily pains and headaches on their health. The study recommends that kitchen staff be educatedon the concept of their kitchen layout and the associated benefits to boost productivity.